Moderate‐ and High‐Intensity Exercise Improves Lipoprotein Profile and Cholesterol Efflux Capacity in Healthy Young Men - Kelly M. Stanton; Vivian Kienzle; Donna Lee M. Dinnes; Irina Kotchetkov; Wendy Jessup; Leonard Kritharides; David S. Celermajer; Kerry‐Anne Rye (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background Exercise is associated with a reduced risk of cardiovascular disease. Increased high‐density lipoprotein cholesterol (HDL‐C) levels are thought to contribute to these benefits, but much of the research in this area has been limited by lack of well‐controlled subject selection and exercise interventions. We sought to study the effect of moderate and high‐intensity exercise on HDL function, lipid/lipoprotein profile, and other cardiometabolic parameters in a homogeneous population where exercise, daily routine, sleep patterns, and living conditions were carefully controlled. Methods and Results Male Army recruits (n=115, age 22±0.3 years) completed a 12‐week moderate‐intensity exercise program. A subset of 51 subsequently completed a 15‐week high‐intensity exercise program. Fitness increased and body fat decreased after moderate‐ and high‐intensity exercise (P<0.001). Moderate‐intensity exercise increased HDL‐C and apolipoprotein A‐I levels (6.6%, 11.6% respectively), and decreased low‐density lipoprotein cholesterol and apolipoprotein B levels (7.2%, 4.9% respectively) (all P<0.01). HDL‐C and apolipoprotein A‐I levels further increased by 8.2% (P<0.001) and 6.3% (P<0.05) after high‐intensity exercise. Moderate‐intensity exercise increased ABCA‐1 (ATP‐binding cassette transporter A1) mediated cholesterol efflux by 13.5% (P<0.001), which was sustained after high‐intensity exercise. In a selected subset the ability of HDLs to inhibit ICAM‐1 (intercellular adhesion molecule‐1) expression decreased after the high (P<0.001) but not the moderate‐intensity exercise program. Conclusions When controlling for exercise patterns, diet, and sleep, moderate‐intensity exercise improved HDL function, lipid/lipoprotein profile, fitness, and body composition. A sequential moderate followed by high‐intensity exercise program showed sustained or incremental benefits in these parameters. Improved HDL function may be part of the mechanism by which exercise reduces cardiovascular disease risk.